Rancang Bangun Aplikasi Edukasi Interaktif Untuk Jogging Berbasis Android - Lubis, Farhan Rusdy Asyhary; Syuhada, Muhammad Randa; Triase, Triase (Jurnal Ilmiah Sains dan Teknologi, 2024)
The design of an interactive educational application for jogging based on Android, is an application created to make it easier for people to know about the definition of jogging and the health benefits of jogging, this application was created with a smart apps creator and the Canva application which aims to make it easier for writers to create educational applications This interactive, the final result of this interactive educational application design project will use mobile device media, namely Android-based. The author raised this title because the author saw a lack of public awareness about exercising, especially jogging, therefore the author took the initiative to raise the title of creating this interactive educational application so that people know the importance of jogging.